2016
DOI: 10.1371/journal.pntd.0004633
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Spatio-temporal Patterns of Dengue Transmission from Surveillance Data in Guangzhou, China

Abstract: BackgroundDengue is a serious vector-borne disease, and incidence rates have significantly increased during the past few years, particularly in 2014 in Guangzhou. The current situation is more complicated, due to various factors such as climate warming, urbanization, population increase, and human mobility. The purpose of this study is to detect dengue transmission patterns and identify the disease dispersion dynamics in Guangzhou, China.MethodologyWe conducted surveys in 12 districts of Guangzhou, and collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 43 publications
3
47
0
1
Order By: Relevance
“…Based on temperature-controlled mosquito experiments of Yang et al [25], a series of theoretical analysis were published utilizing these novel data to inform more flexible approaches to understanding temperature effects on various life history traits [2630]. In recent two years, some researches on 2014 Guangzhou outbreak data (only including the symptomatic data) were published [3134]. Sang et al [31, 32] claimed that the number of imported cases, minimum temperature with a one-month lag and cumulative precipitation with a three month lag predicted the outbreak in 2013 and 2014 by using a multivariate Poisson regression analysis of the Guangzhou outbreak data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on temperature-controlled mosquito experiments of Yang et al [25], a series of theoretical analysis were published utilizing these novel data to inform more flexible approaches to understanding temperature effects on various life history traits [2630]. In recent two years, some researches on 2014 Guangzhou outbreak data (only including the symptomatic data) were published [3134]. Sang et al [31, 32] claimed that the number of imported cases, minimum temperature with a one-month lag and cumulative precipitation with a three month lag predicted the outbreak in 2013 and 2014 by using a multivariate Poisson regression analysis of the Guangzhou outbreak data.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [33] used a mathematical model to obtain that climate and the timing of imported cases as the causal factors of dengue outbreak in Guangzhou (The authors assumed that only one case was imported to Guangzhou in the model, this assumption was actually wrong). Zhu et al [34] found that urbanization, vector activities, and human behavior play significant roles in shaping the dengue outbreak and the patterns of its spread by using a spatio-temporal patterns model. In recent study, Chastel [35] concluded that asymptomatic dengue infections could cause new foci of disease or eventually an epidemic in non-endemic regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies concluded that weather conditions were the primary driver of DENV transmission 19,20 , whereas others concluded that importation patterns, delayed outbreak response, or both importation patterns and delayed outbreak response were causal drivers of the 2014 epidemic [21][22][23] . Still others found that neither weather conditions nor importation were key drivers of transmission, but instead that urbanization was pivotal 24,25 . Two analyses 19,20 that used incidence data aggregated at a monthly time scale for 2005-2015 showed high predictive capability at one-month lead times but did not facilitate clear interpretation of how importation interacts with local conditions to result in high inter-annual variation in transmission.…”
mentioning
confidence: 99%
“…Two analyses 19,20 that used incidence data aggregated at a monthly time scale for 2005-2015 showed high predictive capability at one-month lead times but did not facilitate clear interpretation of how importation interacts with local conditions to result in high inter-annual variation in transmission. Mechanistic models applied to date have used daily or weekly data, but only for 2013-2014, and therefore only considered years with anomalously high transmission 21,[23][24][25] . As a result, it is unclear how well those models could explain the strikingly low incidence observed in years other than 2013-2014.…”
mentioning
confidence: 99%